Antonin Artaud ou l’absence à soi-même et l’expérience du vide - Rougé, Dominique (Quêtes littéraires, 2011)
Concerning Antonin Artaud it has been question of some lack of work but in the article we propose to the reading we are talking about another kind of absence. Indeed, in his correspondence and in the writings of his youth, the poet was complaining to be absent to himself. He was saying that words could not convey what he felt, that he had the impression to be a spectator of himself. Over time, he will say that he was feeling some emptiness in him. Is it to fill this emptiness that he spent his time writing on notebooks and that he had replaced speaking by screaming? As a conclusion to this article, we spend some time thinking about the concepts of absence and emptiness, following some writings of Pierre Fédida.